A phylogenomic and comparative genomic analysis of Commensalibacter, a versatile insect symbiont - Juliana Botero; Atena Sadat Sombolestani; Margo Cnockaert; Charlotte Peeters; Wim Borremans; Luc De Vuyst; Nicolas J. Vereecken; Denis Michez; Guy Smagghe; German Bonilla-Rosso; Philipp Engel; Peter Vandamme (Animal Microbiome, 2023)
Abstract Background To understand mechanisms of adaptation and plasticity of pollinators and other insects a better understanding of diversity and function of their key symbionts is required. Commensalibacter is a genus of acetic acid bacterial symbionts in the gut of honey bees and other insect species, yet little information is available on the diversity and function of Commensalibacter bacteria. In the present study, whole-genome sequences of 12 Commensalibacter isolates from bumble bees, butterflies, Asian hornets and rowan berries were determined, and publicly available genome assemblies of 14 Commensalibacter strains were used in a phylogenomic and comparative genomic analysis. Results The phylogenomic analysis revealed that the 26 Commensalibacter isolates represented four species, i.e. Commensalibacter intestini and three novel species for which we propose the names Commensalibacter melissae sp. nov., Commensalibacter communis sp. nov. and Commensalibacter papalotli sp. nov. Comparative genomic analysis revealed that the four Commensalibacter species had similar genetic pathways for central metabolism characterized by a complete tricarboxylic acid cycle and pentose phosphate pathway, but their genomes differed in size, G + C content, amino acid metabolism and carbohydrate-utilizing enzymes. The reduced genome size, the large number of species-specific gene clusters, and the small number of gene clusters shared between C. melissae and other Commensalibacter species suggested a unique evolutionary process in C. melissae, the Western honey bee symbiont. Conclusion The genus Commensalibacter is a widely distributed insect symbiont that consists of multiple species, each contributing in a species specific manner to the physiology of the holobiont host.